Pengolahan Data Keuangan Menggunakan Zahir Accounting 5.1 Pada PT. Ekapersada Abadi - Rifky Permana; Intan Puji Christanti; Sri Diana (LPPM Universitas Bina Sarana Informatika, 2022)
The development of increasingly advanced technology, influence various aspects of the business world. Computers and software are examples of technology that has a very big role in a company. These devices are interconnected to help complete various kinds of work quickly, efficiently and accurately. PT Ekapersada Abadi is a company in the field of general suppliers and construction. This company has been computerized in a simple way by utilizing computers in carrying out financial data processing. In its implementation the software used is Microsoft Excel. The process of making recaps of transactions, inventories, general journals, ledgers and financial reports is done by entering data into Microsoft Excel one by one so that there are often obstacles such as multiple inputs, recording errors, difficulties in finding data, and the need for a long time in preparing financial reports. To solve the problems faced, this company requires a special accounting application that is easy to apply and learn. Zahir Accounting version 5.1 application is the right solution to solve the problems that exist in this company. This application is easy to apply and learn, namely by inputting company data and financial data automatically journals, ledgers, financial reports and business analysis will be formed.